2017
DOI: 10.1615/critrevimmunol.2017019636
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Forkhead Box 1 (FOXO1) in the Immune System: Dendritic Cells, T Cells, B Cells, and Hematopoietic Stem Cells

Abstract: Forkhead box-O (FOXO) transcription factors have a fundamental role in the development and differentiation of immune cells. FOXO1 and FOXO3 are FOXO members that are structurally similar and bind to the same conserved consensus DNA sequences to induce transcription. FOXO1 has been studied in detail in the activation of dendritic cells (DCs), where it plays an important role through the regulation of target genes such as ICAM-1, CCR7, and the integrin αvβ3. FOXO1 is activated by bacteria challenge in DCs and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 78 publications
4
47
0
Order By: Relevance
“…Since the discovery of the first Forkhead gene in Drosophila in 1989, more than 100 members of the family have been identified [31]. The common feature of the Forkhead family is a conserved DNA-binding domain called Fox, which consists of three α-helices, three β-sheets and two loops that are referred to as wings [32,33]. Because of this feature, these transcription factors are called Forkhead/ winged helix transcription factors.…”
Section: Akt Target Proteinsmentioning
confidence: 99%
“…Since the discovery of the first Forkhead gene in Drosophila in 1989, more than 100 members of the family have been identified [31]. The common feature of the Forkhead family is a conserved DNA-binding domain called Fox, which consists of three α-helices, three β-sheets and two loops that are referred to as wings [32,33]. Because of this feature, these transcription factors are called Forkhead/ winged helix transcription factors.…”
Section: Akt Target Proteinsmentioning
confidence: 99%
“…2i). Of note, FOXO1 regulates oxidative stress responses, proliferation, cell survival, and apoptosis, and connects metabolic activity with immune response [38][39][40] .…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that a cascade involving kinase Mst-Foxo/nuclear factor 2 (Nrf2) signaling pathway is important for attenuating ROS-induced immune cell damage and pathological states including infection diseases. Up regurlation of Foxo3 was reported to modulate helper T cell quiescence [ 85 ] and increase T-lymphocyts apoptosis [ 86 ]. Bi et al [ 87 ] indicated that Foxo1, Foxo3 and Foxo4 are key genes in inhibiting lymphocyte cell proliferation of chicken infected with reticuloendotheliosis virus.…”
Section: Discussionmentioning
confidence: 99%